The effect of per capita GRDP, HDI, and labor force participation rate on income inequality in Lampung Province 2019–2023 - Desmon, Desmon; CN, Yudhinanto; Hasbullah, Hasbullah; Alie, Maria Septijantini (ARKA INSTITUTE, 2025)
For a long time, many nations have struggled with the intricate issue of income disparity. Income inequality is a problem in a number of Indonesian provinces. Disparities in the economic well-being of a community are the root cause of income inequality. Income inequality in Lampung Province from 2019 to 2023 is the target of this research, which tries to pin down the relationship between GRDP per capita, HDI, and TPAK. The study makes use of panel data and quantitative approaches. Fifteen districts and cities in Lampung Province provide 75 samples for the panel data, which includes time series data from 2019 to 2023 as well as cross-sectional data. The following statistical methods are used in data analysis: F-test, t-test, coefficient of determination assessment, multiple linear regression, and classical assumption testing. The results show that from 2023 to 2029, the following variables have a significant impact on Income Distribution Inequality in Lampung Province: Gross Regional Domestic Product per capita, Human Development Index, and Labor Force Participation Rate. Income Inequality in Lampung Province 2019–2023, to a lesser extent, is affected by GRDP Percapita. Income Inequality in Lampung Province 2019–2023, to a lesser extent but still significantly, is affected by the Human Development Index. From 2019 to 2023, the income inequality in Lampung Province is affected, to a lesser but considerable extent, by the labor force participation rate.